Sea Salts Flavored with Mediterranean Herbs and Fruits Prevent Cholesterol and Phospholipid Membrane Oxidation and Cell Free Radical Generation. Issue 4 (20th February 2018) - Rosa, Antonella; Putzu, Danilo; Atzeri, Angela; Cesare Marincola, Flaminia; Sarais, Giorgia
Abstract : The authors evaluated and compared, with respect to normal salt, the antioxidant activity of commercial sea salts flavored with Mediterranean herbs and fruits in chemical models of lipid peroxidation and in cell cultures. Salts flavored with myrtle, rosemary, and a mixture of herbs/plants preserves liposomes from Cu 2+ ‐induced oxidation. Methanol extracts obtained from all flavored sea salts significantly reduces the reactive oxygen species generation in Caco‐2 cells, while extracts obtained from myrtle, rosemary, and mixed herbs/plants salts prevents cholesterol oxidative degradation (140 °C). 1 H NMR spectroscopy led to the identification of carbohydrates, organic acids, and amino acids in salt extracts. The phenol content of flavored salts is estimated by the Folin–Ciocalteu procedure and HPLC–DAD analyses. The results of this work assess the potential antioxidant role and health benefits of the use of flavored sea salts in foods instead of normal salt. Practical Applications : This preliminary study evidences that the addition of sea salts flavored with Mediterranean herbs and fruits to food products could represents a strategy to preserve salt‐induced lipid oxidation and a source of antioxidants with potential health benefits. Four sea salts flavored with Mediterranean herbs/plants and fruits inhibit cholesterol/liposomes oxidation and reduce cell ROS generation. Abstract : Four sea salts flavored with Mediterranean herbs/plants and fruits inhibit cholesterol/liposomes oxidation and reduce cell ROS generation.